Legal Obligations of Contractors in Construction Projects: Analyzing the Conflict of Legal Compliance, Contract Performance, and Quality Assurance in Construction Services in Indonesia - Anggi Ismail Sidik (Proceedings Series on Social Sciences & Humanities, 2023)
Construction quality is a crucial aspect of the construction industry in Indonesia, as it directly affects the safety, durability, and functionality of built structures. This research proposal aims to examine the obligations of contractors in ensuring construction quality in Indonesia, specifically focusing on the provisions outlined in Law Number 2 of 2017 on Construction Services. This research aims to investigate the obligations of contractors in guaranteeing construction quality in Indonesia, with a specific focus on the provisions outlined in Law Number 2 of 2017 on Construction Services. The objective of the study is to analyze the legal obligations imposed on contractors and examine their practical implementation in ensuring construction quality. The research employs a juridical-empirical research method, combining legal analysis of the relevant legal provisions with empirical data collection through interviews and document analysis. The research findings will contribute to an improved understanding of the responsibilities and roles of contractors in upholding construction quality, identify any gaps in the existing legal framework, and provide insights for potential enhancements in the enforcement mechanisms to strengthen construction quality management practices in Indonesia.